THE EFFECTIVENESS OF FUNDAMENTAL RIGHTS IN TIMES OF CRISIS: AN ANALYSIS BASED ON THE ECONOMIC-HERMENEUTIC PENDULUM THEORY - Ruas Abreu Areal Marques, Pedro Henrique; Teixeira Oliveira Ruas, Ana Carolina (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
The present study aims to elucidate the issue of fundamental rights in times of crisis, where they are commonly mitigated under the justification of problems of effectiveness, such as the scarcity of resources. Thus, we propose the analysis of such statements under the framework of the work Theory of the Economic-Hermeneutic Pendulum by Cláudio Carneiro Bezerra Pinto Coelho, which proposes the search for a concrete answer to the effectiveness of fundamental rights. Thus, the study will address general aspects of fundamental rights. And it will also analyze the elements that demonstrate obstacles to the realization of fundamental rights. And finally, it will address the Theory of the Economic-Hermeneutic Pendulum and its contributions to the analysis of fundamental rights in crisis situations. It is concluded that such a theory is of great importance to the realization of fundamental rights, since it proposes a correct answer of a practical-theoretical nature through the appropriate question, thus proposing a possible justice. For that, the phenomenological method and bibliographical research were used.